2022
DOI: 10.1136/bmjgh-2021-007731
|View full text |Cite
|
Sign up to set email alerts
|

Mother and newborn skin-to-skin contact in sub-Saharan Africa: prevalence and predictors

Abstract: IntroductionSkin-to-skin contact is an evidence-based intervention that signifies a situation whereby a newborn is positioned directly on the mother’s abdomen or chest in order for them to have direct ventral-to-ventral skin contact. The act of skin-to-skin contact begins immediately after delivery to about 23 hours afterwards. Evidence shows that skin-to-skin contact is important in improving child health outcomes. Nevertheless, evidence on its prevalence and predictors in sub-Saharan Africa (SSA) remains spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 37 publications
(61 reference statements)
3
9
2
Order By: Relevance
“…Only weight taking at birth and assessing the child’s health at discharge had higher coverage rates among the interventions. It is important to note, however, that the current study’s coverage of early breastfeeding initiation and immediate skin-to-skin contact is higher than previously reported [ 25 , 26 ]. We also found that coverage of five interventions: early breastfeeding initiation within 1 h after birth, immediate skin-to-skin contact, cord examination, temperature taking, and checking the child’s health before discharge differed substantially by provider type.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Only weight taking at birth and assessing the child’s health at discharge had higher coverage rates among the interventions. It is important to note, however, that the current study’s coverage of early breastfeeding initiation and immediate skin-to-skin contact is higher than previously reported [ 25 , 26 ]. We also found that coverage of five interventions: early breastfeeding initiation within 1 h after birth, immediate skin-to-skin contact, cord examination, temperature taking, and checking the child’s health before discharge differed substantially by provider type.…”
Section: Discussioncontrasting
confidence: 70%
“…Similarly, it was observed that women exhibited decreased likelihood to commence skin-to-skin contact and initiate early breastfeeding when their neonates presented with an Apgar score of less than seven at one minute post-delivery [ 33 ]. Low birthweight infants, on the other hand, were more likely to engage in immediate skin-to-skin contact with their mothers than babies born with a normal birthweight [ 25 ]. Furthermore, it was observed that singleton births were associated with a higher likelihood of initiating early breastfeeding compared to multiple births or twin deliveries [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Early initiation of BF has been shown to promote EBF, 42 while the long‐time duration for initiation of BF implies that a prelacteal food must have been introduced 54 . Mother and newborns skin‐to‐skin contact have been found to positively influence the timely initiation of BF in various countries, including Angola, Cameroon, Ethiopia, Guinea, Liberia, Malawi, Mali, Sierra Leone, South Africa, Tanzania, Uganda, Zambia, and Zimbabwe 58 . Mothers who initiated BF within 1 h of giving birth, and practised skin‐to‐skin contact, tend to practice EBF 33,58 .…”
Section: Resultsmentioning
confidence: 99%
“…54 Mother and newborns skin‐to‐skin contact have been found to positively influence the timely initiation of BF in various countries, including Angola, Cameroon, Ethiopia, Guinea, Liberia, Malawi, Mali, Sierra Leone, South Africa, Tanzania, Uganda, Zambia, and Zimbabwe. 58 Mothers who initiated BF within 1 h of giving birth, and practised skin‐to‐skin contact, tend to practice EBF. 33 , 58 However, late initiation of BF was common among those who did not utilize healthcare services and those with lower incomes.…”
Section: Resultsmentioning
confidence: 99%
“…Growing number of researchers have been focusing on exploring new care models in NICU to reduce the negative influence of maternal separation(Aboagye et al, 2022; McKenzie et al, 2022; Taylor et al, 2022). Family integrated care (FICare) is an upgraded family centered care model for preterm infants in NICU by integrating parents into the NICU care team as primary caregivers during infants' hospital stay (Franck et al, 2020).…”
Section: Introductionmentioning
confidence: 99%